Servo motor angle control in an automatic droplet system for quantum dot sintesis - Al Rasyid, Syahrul; Asnil (Department of Electrical Engineering Universitas Negeri Padang, 2025)
This research aims to develop an automation system in the synthesis process of core-shell quantum dots using the Arduino-based hot injection method. The system is designed to resemble an automatic syringe pump consisting of an Arduino UNO microcontroller, servo motor, LCD, and toggle switch to control the rate of solution injection precisely within a certain time range. The servo motor regulates the movement of the syringe to produce drops of solution according to the selected duration, ranging from 1 to 24 hours. The test results show that the system can execute 21 servo rotations forward at an angle of 22° per rotation and 4 backward at an angle of 115° per rotation, with high accuracy and time stability. The time display on the LCD showed good agreement with the real time, proving the effectiveness of the monitoring and control system. The system was able to improve the efficiency and precision of the QD synthesis process compared to the manual method, and showed great potential in automation applications in the field of materials chemistry